Pengaruh Experiential Marketing Terhadap Pembelian Ulang Produk Lakuna Kopi - Muhammad Raffi; Joseph M.J. Renwarin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This purpose aims to determine how much influence the experiential marketing has on repurchasing Lakuna Kopi products. This research is a quantitative study using the SPSS Statistics 20 program with a sample of 160 respondents who are Lakuna Coffee consumers who have already made repeat purchases using nonprobability sampling and purposive sampling techniques. From the results of the hypothesis analysis it states that experiential marketing has a significant effect on repeat purchases; the five experiential marketing sub-variables have a significant simultaneous re-purchase effect. Judging from Sense Marketing, researchers suggest that Lakuna Kopi owners make cleanliness (SM3) an important point